Audit Manajemen Keamanan Teknologi Informasi Menggunakan Standar ISO 27001 : 2005 Di PerguruanTinggi XYZ - Sidik, Muhammad; Iriani, Ade; Yulianto, Sri (LPPM UNIKA Santo Thomas Medan, 2018)
Management audit is very important for any colleges towards the examination and assesment of their information technology management to gain efficient and effective business running process. Information technology security as an effort of internal controlling for risk and threat security minimization, is mainly considered due to all learning and lecturing administration activities use information technology. To find out how secure technology information is, it is then recquiring an audit to make sure everything run based on procedure. Standard used is framework international standardization organization (ISO) 27001:2005. It ischosen because framework can be adjusted with instrument of the research used in the organization. It is then developed and focused on information security management system (SMKI). As a results, all have outcome JPA = PA1:PA10, NA=JPA/10 produces value average 65%. Last but not at least, it showspositive level, but still under expectation by college requirement that requires continuous evaluation and enhancement of recommended security control